Functional Outcome Of Reconstruction Of Coracoclavicular And Acromioclavicular Ligaments In Acromioclavicular Joint Dislocation - Manandhar, Rajeev Raj; Manandhar , Rajeev Raj; Gautam, Saroj; Khanal , Krishna Raj; Khanal, Himal (Nepal Journal of Medical Sciences, 2021)
Introduction: Acromioclavicular joint dislocations account for approximately 12% of injuries to the shoulder girdle. Reconstruction of these dislocations is advised and various authors have described different techniques. The modern approach has emphasized anatomic reconstruction using semitendinosus autograft. Methods: Adults with chronic acromioclavicular joint dislocation presenting to our hospital underwent reconstruction of the joint. A standard protocol of surgery and post-operative rehabilitation was followed. The functional outcome was assessed using the Constant-Murley shoulder score after six months. Results: A total of twenty-one patients were evaluated. The functional outcome was assessed at 24 weeks using the Constant-Murley score. Nineteen patients (90.4%) had a very good outcome, one patient had a good outcome whereas one had a fair outcome. Conclusion: The anatomic reconstruction of the acromioclavicular joint using semitendinosus graft results in very good outcomes with few complications.